Current Pharmacological Treatment Options for Central Serous Chorioretinopathy: A Review - Massimo Nicolò; Lorenzo Ferro Desideri; Aldo Vagge; Carlo Enrico Traverso (MDPI AG, 2020)
Central serous chorioretinopathy (CSC) is a common cause of visual impairment in patients generally aged 20 to 60 and it is characterized by acute or chronic neurosensory detachments of the retina. Although CSC resolves spontaneously in most cases, in some patients it may cause permanent visual impairment in the working population; for this reason, several approaches, including photodynamic therapy (PDT), subthreshold micropulse laser treatment and oral mineralocorticoid receptor antagonists, have been studied as first-line treatment options for CSC. To date, half-dose PDT has provided the most encouraging results in this regard, supported by large, multicenter, randomized clinical trials such as the "Prospective Randomized Controlled Treatment Trial for Chronic Central Serous Chorioretinopathy" (PLACE) trial; however, the role of novel possible non-invasive treatment options is attracting interest. This review article aims to discuss the current pharmacological treatment options investigated for the management of CSC, including aspirin, ketoconazole, beta blockers, rifampicin and many others. In particular, further evidence about oral mineralocorticoid receptor antagonists, firstly seen as promising non-invasive alternatives for treating CSC, will be provided and discussed in light of the recent "Eplerenone for chronic central serous chorioretinopathy in patients with active, previously untreated disease for more than 4 months" (VICI) trial results, which have largely resized their role as possible first-line oral treatment options for treating CSC.